Compensatory recombination phenomena of neurological functions in central dysphagia patients - Yuan, Xiao-dong; Zhou, Li-fu; Wang, Shu-juan; Zhao, Yan-sheng; Wang, Xiao-jie; Zhang, Li-li; Wang, Shou-hong; Zhang, Ya-jie; Chen, Li (Neural regeneration research, 2015)
We speculate that cortical reactions evoked by swallowing activity may be abnormal in patients with central infarction with dysphagia. The present study aimed to detect functional imaging features of cerebral cortex in central dysphagia patients by using blood oxygen level-depen- dent functional magnetic resonance imaging techniques. The results showed that when normal controls swallowed, primary motor cortex （BA4）, insula （BA13）, premotor cortex （BA6/8）, supramarginal gyrus （BA40）, and anterior cingulate cortex （BA24/32） were activated, and that the size of the activated areas were larger in the left hemisphere compared with the right. In re- current cerebral infarction patients with central dysphagia, BA4, BA13, BA40 aild BA6/8 areas were activated, while the degree of activation in BA24/32 was decreased. Additionally, more areas were activated, including posterior cingulate cortex （BA23/31）, visual association cortex （BA18/19）, primary auditory cortex （BA41） and parahippocampal cortex （BA36）. Somatosen- sory association cortex （BA7） and left cerebellum in patients with recurrent cerebral infarction with central dysphagia were also activated. Experimental findings suggest that the cerebral cortex has obvious hemisphere lateralization in response to swallowing, and patients with recurrent cerebral infarction with central dysphagia show compensatory recombination phenomena of neurological functions. In rehabilitative treatment, using the favorite food of patients can stimu- late swallowing through visual, auditory, and other nerve conduction pathways, thus promoting compensatory recombination of the central cortex functions.